An integrative perspective on the interplay between early maladaptive schemas and mental health: The role of self‐compassion and emotion regulation. Issue 6 (8th February 2019) - Yakın, Duygu; Gençöz, Tülin; Steenbergen, Laura; Arntz, Arnoud
Abstract: Objectives: We aimed to test whether negative emotion regulation difficulties and self‐compassion mediate the relationship between early maladaptive schemas (EMSs) and symptoms of psychopathology and life satisfaction. Methods: Data were collected from 296 adults (179 females, 117 males), whose age ranged from 17 to 52 years. The mediating roles of self‐compassion and negative emotion regulation were examined via Hayes' procedure (PROCESS) for multiple mediation. Results: Negative emotion regulation was the only mediator to psychopathological symptoms, with no additional role for self‐compassion, whereas self‐compassion mediated only to life satisfaction, with no additional role for negative emotion regulation. Conclusions: The results provide evidence for unique mediating roles of negative emotion regulation and self‐compassion, depending on the outcome variable. That helps to understand how problems that may be identified in terms of positive and negative domains are related to EMSs, and allows to put forward potential strategies within the frame of schema therapy.